(untitled) (Gayana Botánica, 2000)
Samples of Pinguicula chilensis (Lentibulariaceae) where collected from the Cordillera de Nahuelbuta in order to characterized some of its anatomical features. Leaves where processed for scanning electrom microscopy analysis in which pedunculated trichomes and secrecetory glands form 4-8 cells could be observed.